TIPOLOGI PEMIKIRAN MODERNIS PENDIDIKAN ISLAM - Andik Wahyun Muqoyyidin (el-hikmah, 2011)
Among the philosophers of education in general, as Broudy (1961) states that the philosophy of education is seen as a systematic discussion about education issues at a philosophical level, which is investigating the issue of education until reduced to the subject matter of metaphysics, epistemology, ethics, logic, aesthetics or a combination of all these. In the discussion of philosophy of education, these problems can be simplified into three main issues, namely the view of the reality studied by metaphysics or ontology, the view of the knowledge learned by the epistemology, and views on values learned by the axiology. On the other hand, the development of thinking  Islamic education can be seen from the pattern of Islamic thought that flourished in the Islamic world in this modern period, especially the challenging and changing times and the era of modernity. Accordingly, Abdullah (1996) examine the existence of four models of Islamic thought, namely (1) textual Salafi Model, (2) Mazhabi traditionalists Model, (3) Modernist Model, and (4) Neo-Modernist Model. Typology further highlight the modernist Islamic educational insights modification free, progressive and dynamic in the face and respond to the demands and needs of their communities, so that Islamic education serves as an attempt to reconstruct a continuous experience, in order to do something intelligent and able to make adjustments and readjustments in accordance with the demands and needs of the environment in the present.